(untitled) - Thomas, Roy (Canada, 1989)
In Japan: The Blighted Blossom, Roy Thomas reveals the reality behind the faade of a stable democracy, a rigorous education system, and an "economic miracle" within which managers and workers coexist in workaholic harmony. Patronage, bribery, and blackmail undermine democracy, and a rigid, authoritarian environment oppresses workers. While debunking many of Japan's official myths, Thomas displays an unmistakeable empathy for the Japanese people and staunch support for their efforts to build a genuine democracy.The first popular book in English to explain why Japan's chance at democracy may be lost.
Keywords: Japan; History; 1945-